(untitled) (Proceedings of the International Conference on Public Health, 2019)
Agricultural sector only contributed 14.43% of total GDP despite labor from this sector is the largest labor force in Indonesia. Cocoa is one of the leading commodities in agricultural sector, sub sector plantation. One of the ways to improve the productivity of cocoa is giving an attention about the good nutrition and good health of the cocoa farmer that have been widely known as a factor to improve work productivity of farmers. This study is cross-sectional study. The objective of this study was to analyze the relationship between nutritional status, health status, food consumption, and lifestyle to work productivity. The subjects were 58 male cocoa farmers in two districts of Polewali Mandar aged 18-65 years old. Most of subjects (39.7%) have a normal nutritional status and 10.3% of subjects are central obesity. Then, 46.6% of subjects have a pre-hypertension. There is no relationship between nutritional statuses to work productivity. Then, there is a relationship between health status (blood pressure) and amount of cocoa picked per day (kilograms) and health status (central obesity) and number of absent days to plantation due to sick